2017
DOI: 10.1002/2327-6924.12507
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs in obesity management

Abstract: Despite the rather slow acceptance of obesity as a disease state, several obesity staging systems and weight‐management guidelines have been developed and are in use, along with an ever‐growing number of treatment options. Many primary care clinicians, including nurse practitioners (NPs), are at the forefront of clinical efforts to assist individuals with obesity, but face challenges due to lack of alignment and consensus among the various staging systems and guidelines. This is further complicated by shortfal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
(85 reference statements)
2
9
0
1
Order By: Relevance
“…It appears as a self-fulfilling prophecy. This is in accordance with other studies that examined weightrelated challenges dating back to adolescence (Malterud & Ulriksen, 2010;Ritten & LaManna, 2017). Hofmann (2016) found that food and eating are phenomena with strong cultural bearings and that they are profoundly private.…”
Section: To Be Alienated As a Human Beingsupporting
confidence: 91%
“…It appears as a self-fulfilling prophecy. This is in accordance with other studies that examined weightrelated challenges dating back to adolescence (Malterud & Ulriksen, 2010;Ritten & LaManna, 2017). Hofmann (2016) found that food and eating are phenomena with strong cultural bearings and that they are profoundly private.…”
Section: To Be Alienated As a Human Beingsupporting
confidence: 91%
“…Our results showed that overweight or obese patients were at risk of deteriorating the satisfaction of needs. High levels of unmet needs in obese patients were also reported in previous studies [ 44 ]. It is known that obesity is a causative factor in a diverse range of comorbid diseases.…”
Section: Discussionsupporting
confidence: 74%
“…Obesity is a chronic, relapsing, progressive disease (1) with a multifactorial origin, including genetic, metabolic, behavioral, sociocultural, and environmental factors (2,3). The clinical complications of obesity include cardiovascular diseases (CVD; e.g., ischemic heart disease, heart failure), metabolic diseases (type 2 diabetes [T2D]), mechanical dysfunction (musculoskeletal disorders [e.g., osteoarthritis]), sleep apnea, and malignancy (4‐7). Around 13% to 19.5% of adults globally have obesity, and the prevalence of obesity is predicted to continue to rise (5,8).…”
Section: Introductionmentioning
confidence: 99%